Antinociceptive and anti-inflammatory effects of Lonicera japonica thunb. - Sulaiman, Mohd Roslan; Zakaria, Zainul Amiruddin; Moin, Saidi; Somchit, Muhammad Nazrul; Chai, Y. S. (Medwell Publishing, 2008)
The present study was carried out to establish the antinociceptive and anti-inflammatory activities of the aqueous extract of Lonicera japonica flowers' buds in various experimental animal models. The antinociceptive activity was measured using the abdominal construction, hot plate and formalin tests, while, the anti-inflammatory was measured using the carrageenan-induced paw edema. The dried flower's buds of L.japonica was added with distilled water (1:10 w v-1) and boiled for 2 h at 80°C. The supernatant collected was freeze-dried overnight and prior to use was diluted to the desired doses. The extract (30, 100 and 300 mg kg-1; administered intraperitoneally) exhibited significant (p<0.05) antinociceptive and anti-inflammatory activities in all assays used. In conclusion, the flower's buds of L. japonica possessed potential antinociceptive and anti-inflammatory activities that require further in-depth studies.